2012
DOI: 10.1200/jco.2011.38.9957
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Angioedema and Marginal Zone Lymphoma

Abstract: An 80-year-old white female patient presented with severe intermittent abdominal cramps. She described episodes of pain and nausea that lasted up to 12 hours every 4 to 6 weeks. The pain was unremitting in the periumbilical and lower abdominal area, produced bowel urges, and was unrelieved after bowel movements. She made no reports of having constipation, diarrhea, or bloody stools. The cramps were not associated with vomiting, angina, diaphoresis, dyspnea, or constitutional symptoms.Her past medical history w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 14 publications
1
13
0
1
Order By: Relevance
“…In a recent publication from the French National Reference Centre for Angioedema, 7 patients were described with a complete clinical efficacy in 3, partial in 2 and therapeutic failure in another 2 patients [12]. Levi et al [32] published 3 AAE patients who went into complete clinical remission, and single case reports can be found too [33,34,35]. One may assume that the treatment efficacy is dependent on the existence of anti-C1INH autoantibodies as a basic pathogenic factor, because RTX may disrupt the anti-C1INH antibody formation.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication from the French National Reference Centre for Angioedema, 7 patients were described with a complete clinical efficacy in 3, partial in 2 and therapeutic failure in another 2 patients [12]. Levi et al [32] published 3 AAE patients who went into complete clinical remission, and single case reports can be found too [33,34,35]. One may assume that the treatment efficacy is dependent on the existence of anti-C1INH autoantibodies as a basic pathogenic factor, because RTX may disrupt the anti-C1INH antibody formation.…”
Section: Discussionmentioning
confidence: 99%
“…Icatibant is a novel therapeutic option for AAE patients who inadequately respond to current therapies. Rituximab treatment has been used in small series of AAE patients and the results seem to be promising, (83,84) however controlled studies are lacking.…”
Section: Conventional Managementmentioning
confidence: 98%
“…However, the treatment of any lymphoproliferative or autoimmune disorder in AAE patients has usually proved successful in inducing partial or complete clinical and/or biochemical remission of AAE [44,45]. Recently published studies reported cases of eradication of life-threatening angioedema symptoms in patients suffering from AAE in the setting of low-grade B-cell lymphoma as well as effective clinical and biochemical angioedema remission in the setting of autoimmune disease, thanks to four standard infusions of rituximab (375 mg/m 2 ), inducing depletion of B lymphocytes and subsequent decreased titers of bound and free C1-INH protein auto-reactive immunoglobulins [36,45,46].…”
Section: Treatmentmentioning
confidence: 99%